Hypocalcemia Revealing an Enteropathy-Associated T-cell Lymphoma - Maria Belen Alonso-Ortiz; Noel Lorenzo Villalba; Emilio Almaraz Marroquin; Melek Kechida; Manuel Mendez Bailon; Imanol Pulido Gonzalez (Babol University of Medical Sciences, 2019)
Background: Neurofollicular hamartoma (NFH) is characterized histopathologically by fascicles of spindle cells that laterally delimited by hyperplastic folliculosebaceous units. It usually appears on face, near the nose or nasolabial fold. It does not manifest true neural differentiation and recently the term spindle cell predominant trichodiscoma (SCPT) has been used instead. Case Presentation: We present a case of a 40-year-old male with co-incidence of NFH and basal cell carcinoma (BCC) that the mesenchymal components of NFH were similar to SCPT but these components highly expressed S-100 protein. We also discuss about the histological aspect of the neoplasia in this report and consider the findings of other reports in association with classification of NFH by means of cellular markers and morphological resemblance to other skin hamartomas. Conclusion: Neurofollicular hamartoma is a rare benign tumor that thought to represent the cellular end of a morphological spectrum with trichodiscoma. The morphological features and expression of S100 protein in neural element helped us to achieve the diagnosis of neurofollicular hamartoma. However, variable reports of S-100 protein expression in NFH are available and further studies are needed to determine the classification of this tumor.